One-step conversion of agro-wastes to nanoporous carbons: Role in separation of greenhouse gases. (May 2018) - Saha, Dipendu; Taylor, Bryan; Alexander, Nicole; Joyce, Daniel F.; Faux, Gabriela I.; Lin, Yiting; Shteyn, Vladimir; Orkoulas, Gerassimos
Highlights: Lignin, walnut shell, orange peel and apricot seed were used as carbon precursors. All activated carbons were synthesis in one-step method. The carbons have the BET specific surface areas of 727–2254 m 2 /g. CO2, SF6 and N2 adsorption isotherms were measured on these carbons. Selectivity, binary isotherms and breakthrough times were simulated. Abstract: Highly microporous carbons have been synthesized from four types of agro-wastes of lignin, walnut shells, orange peels and apricot seeds by one-step carbonization/activation with potassium hydroxide (KOH) in varying ratios. The resultant carbons demonstrated BET specific surface areas of 727–2254 m 2 /g, and total pore volumes 0.34–1.14 cm 3 /g. These are higher than the majority of agro-waste derived carbons reported in the literature. For all the carbons, CO2 adsorption at 298 K was higher than SF6 followed by N2 suggesting a possible separation of CO2 and SF6 from N2 . The adsorbed amounts of CO2 at 298 K and 273 K and at pressures up to 760 Torr were 7.24 and 9.4 mmol/g, respectively which, to the best of our knowledge, are the highest CO2 uptakes in these temperatures by any carbon material reported so far. For all the gases, selectivity, mixed adsorption isotherms and adsorption breakthrough have been simulated from experimental data.